THE UTILITY OF CAFÉS IN TOWN FOCUSING ON THE TWO FUNCTIONS OF ‘THE THIRD PLACE’: Received: 8th November 2023 Revised: 20th November 2023, 22nd November 2023 Accepted: 11th November 2023 - Ueda, Mayumi; Akashi, Tatsuo (PEOPLE: International Journal of Social Sciences, 2024)
This study reconsidered the function of town cafés as ‘the Third Place’ from the two perspectives of "a place for exchange" and "a place for emotional support" for city dwellers and clarified the following three points based on user’s consciousness and state of mind. In Japan, it was found that many people use cafés as a place to work alone or recover as "my place" type, and that "my place" type tends to use Chain cafés. Those who use cafés as a place for socializing in the traditional ‘Oldenburg type’ chose privately owned cafés and were found to be highly dependent on them. People who use cafés tend to have higher well-being-related indicators, especially those who use privately owned cafés, than those who use Chain ones.